FALSAFAH IQRA` DALAM SURAH AL-`ALAQ SEBAGAI DASAR EPISTEMOLOGI PENDIDIKAN ISLAM - Adila, Abdan; Mursalim; Yusuf Qardlawi, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the problem of scientific dichotomy in Islamic education which separates revelation and reason. This study aims to reconstruct the philosophy of Iqra' in Surah Al-'Alaq verses 1–5 as the foundation of Islamic education epistemology. This is a library research utilizing thematic exegesis and philosophical approaches. The results show that the philosophy of Iqra' contains three main epistemological principles: (1) Theocentric integration, where the source of knowledge (science and religion) originates from Allah; (2) Validation of scientific methods symbolized by Al-Qalam (pen/research) alongside revelation; and (3) Axiological balance between intellectual intelligence and spiritual awareness. The implications of these findings demand a transformation of the Islamic education curriculum towards integration and a shift in academic culture from rote learning to a research tradition to produce the Ulul Albab generation.